Implementation of Michael Porter's Generic Strategy on Online Business Startups in Social Media Facebook in Kediri and Surrounding Areas - Sugianty Nur Qurrotu Aini; M. Alkirom Wildan (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
Facebook is a social media that is often used by business people in the Kediri area and its surroundings. As many as 53.9% of people use it to open an online business. From the many business actors that appear, the more competitive the environment will be. So, a strategy is needed to be able to win the competition in the environment. This study aims to find out how business actors implement generic strategies for their respective businesses. This study uses a descriptive qualitative method with 3 informants as resource persons. Researchers obtained data by direct observation to the field and conducting oral interviews online. The results of this study indicate that each informant has a tendency towards each generic strategy. The first informant tends to the differentiation strategy, the second informant tends to the low cost strategy and the third informant tends to the focus strategy